TAHAMMUL WA AL-ADĀ’ DALAM PERIWAYATAN HADĪTH - aziz, abd; Terza Travelancya D.P. (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
Abstract Hadith is the second source of law after the Qur'an. Its existence is very urgent when it does not find an explanation in the Qur'an. However, determining whether or not a hadith can be used as evidence (practice) is related to the matan, narrators and sanad. Tahammul wa al-Ada' is one way to determine the quality of the validity of a hadith seen from the connection of the sanad. The tah{ammul wa al-ada' method includes; 1) al-Sama'. 2) al-'Ard or al-Qirā'ah. 3) al-Ijazah. 4) al-Munawalah. 5) al-Mukātabah. 6) I'lam al-Shaikh. 7) al-Wasiyyah. 8) al-Wijādah.